PENGARUH INDEPENDENSI, OBJEKTIVITAS, PENGALAMAN KERJA, KOMPETENSI, INTEGRITAS DAN SKEPTISME PROFESIONALTERHADAP KUALITAS AUDIT (STUDI DI INSPEKTORAT PROVINSI BENGKULU) - Liza Poerwati; Fadli; Nila Aprilla (JURNAL FAIRNESS, 2022)
This study aims to find empirical evidence regarding the effect of independence, objectivity, work experience, competence, integrity and professional skepticism on audit quality at the Bengkulu Provincial Inspectorate. The type of research used in this research is quantitative research. The type of data used is primary data in the form of values or scores for the answers given by respondents to the questions in the questionnaire. The sampling technique used is the saturated sample/census method. Based on sampling through the saturated sample/census method, 46 samples of Bengkulu Province Inspectorate auditors were obtained. The data was processed through the multiple linear regression statistical test method using SPSS software version 21. The results of the study found that competence had a positive effect on audit quality. Meanwhile, independence, objectivity, work experience integrity and professional skepticism have no effect on audit quality.